Tingkat Pemahaman Mahasiswa Terhadap Permainan Futsal - Rahmad Akbar Perdana; Musran Musran (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Futsal is a sports ball played by two teams, each consisting of five players with the aim of inserting a ball into the opponent's goal using the foot, head, and all parts of the body except the hand. As a sport favored by various circles, especially students are important for players to understand the concept and basic techniques of the game Futsal itself. Therefore, this research aims to determine the level of understanding students of Abulyatama University's classification of Futsal. The approach used in this study is qualitative which is descriptive. Samples in the study of 30 people. Data collection is done with a poll consisting of 22 questions in the form of Likert scale with the option of the answer consists of very understanding, understanding, lack of understanding, inunderstanding and very ununderstanding. Data analysis uses frequency distribution formula. The results showed that the student understanding level of Abulyatama University's targeting of the Futsal game with an average of 89.8 is in high category with the following details; (1) As many as 26 respondents were in high category with a percentage rate of 86.66%, as many as 4 respondents were in medium category with a percentage rate of 13.33% and there was no at all the university's health and recreation physical education students Abulyatama belongs to the low category with a percentage rate of 0%. Thus, the level of understanding needs to be maintained by students and the contractor of Abulyatama University's classification study Program to minimize both the study and when performing Futsal game.